Gender differences regarding forming the intent to participate in carbon neutral practices: a nationwide sample study of South Korea - Jin Won Lee; Seungkook Roh (Environmental Research Communications)
For a society to achieve the goal of carbon neutrality, the public must also participate in practices that reduce carbon emissions in their daily lives. This study investigates how males and females differ in forming the intent to participate in such practices. Our analysis of a nationwide survey sample taken from South Korea shows that (1) females have a higher rate of intent to participate in carbon neutral practices; however, (2) the positive effect of the perceived necessity of carbon neutrality on this intent is greater among males. These findings suggest that although males are more restrained regarding their view of carbon neutral practices, their intent to participate in such practices can be greatly increased if they perceive carbon neutrality as necessary. The findings contribute to the existing research on the role of gender in environmental psychology and provide implications for communicating essential information regarding carbon neutral behavior to the general public.